Momentum of Pigeonpea Cultivation in Tripura- an Economics Analysis - Hazari, Sujoy; Ray, Subrata; Das, Partha; De, Biman; Sen, Debashish (Indian Journal of Hill Farming, 2017)
This study on production of Momentum of Pigeonpea cultivation in Tripura- an economics analysis is based on the on secondary data sources and the growth of Pigeonpea was observed over last four decades (1975-76 to 2014-15) data. The net return over Cost A1 have been found to be Rupees 42534.85 per ha and the net return over Cost C3 was Rupees 35179.43 per ha. The return per rupee in over Cost C3 was found to be 2.37 which designate the Pigeonpea is a profitable enterprise for the farming community of Tripura.